Comparative Analysis Of On-Page And Off-Page White Hat Search Engine Optimization (SEO) Techniques On Website Popularity - Aryani, Diah; Shine Pintor Siolemba Patiro; Setiawan, Aji; Tjahjono, Budi (International Journal of Science, Technology & Management, 2023)
Currently, the use of Search Engine Optimization (SEO) has become a necessity to achieve better ranking results from Search Engines known as Search Engine Optimization, which is a collection of techniques for positioning a site so that it can be indexed by search engines and get a position in search engine results—result Pages (SERPs). Based on Globalstatistics data, there has been an increase in internet users in Indonesia who search for products through the search engine market, which has reached 97.38%. This study aims to increase the visibility of a website or multi-umah web page in search results to get a higher ranking on the SERPs in the search results. search results using white hat SEO by comparing on-page techniques and off-page techniques through descriptive qualitative methods, then analyzed using Google Search Console and Google Analytics tools to understand keyword performance, behavior, and customer interests on the umahmulti.biz.id website